Status and Impact of Heavy Metals in Selected Soils and Crops of Kerala - Usha Mathew (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 1999)
Status of Cu, Zn, Ni, Pb and Cd in samples of selected soils, fertilizers, manures and crops were estimated. A critical analysis of the total content of these heavy metals in the soils studied here revealed that Cu arid Cd are existing beyond the critical level in the some of the samples. In the wetland soils, content of all heavy metals was lowest for phytotoxicity and food safety in samples from absolute control plots of rice PME at Pattambi, Moncompu and Kayamkulam and highest in samples from plots receiving maximum quantity of organic manures and inorganic fertilizers. The DTPA extractable form is only a very minor part of their total content. The heavy metal load of the commonly used P fertilizers in Kerala is found to be highly variable. Zn is the highest contaminant followed by Pb, Ni, Cd and Cu. With respect to manures commonly used in Kerala, Zn is the most abundant among the five elements studied followed by Cu. Retention of heavy metals was found to be more in the roots of all plants compared to the above ground portions except Zn in amaranthus. The grain, straw and root of rice plants collected from PME plots which were receiving organic manures and inorganic fertilizers continuously for several years had a distinctly higher content of all heavy metals compared to the samples obtained from absolute control plots. The content of Cu in rice samples and that of Zn and Cu in the fodder samples from sewage farm exceeded the critical level to express phytotoxicity. In some of the samples of amaranthus and cowpea, content of Zn, Pb and Cd exceeded the food safety standards prescribed in Germany.